Poverty and Its Intractability: Causes and Consequences - Ibrahim Musa; Sule Magaji; Chukwuemeka Ifegwu Eke; Oku Abdul-Malik Yakeen (Research Synergy Foundation, 2022)
Poverty is a disease that continues to cause insecurity and other forms of social vices in a country, which in turn affects the growth and development of the nation. The increasing poverty rate, especially in Nigeria, has become a complex problem that has resulted in economic degradation, which must be immediately resolved. Therefore, this study examines poverty and its intractability in Nigeria: causes and consequences. The study analyzes the data using Ordinary Least Square methods. The data were obtained from Federal Reserve Economic Data and the National Bureau of Statistics (NBS). The results indicate that the poverty rate will rise by 0.035375 and 2.564296 units, respectively, for every unit increase in population and unemployment (UMP). Besides, the result shows that a unit increase in the human development index (HDI) will lead to a -4.347621 decrease in the poverty rate in Nigeria. The framework affirms that poverty is an intractability in Nigeria. The study consequently suggests that the government, non-governmental organizations, and private citizens prioritize funding for human development and embrace a solid fiscal policy that will boost economic output and lower the country's degree of poverty.